Short-term predicted extinction of Andean populations of the lizard Stenocercus guentheri (Iguanidae: Tropidurinae). (December 2016) - Andrango, María Belén; Sette, Carla; Torres-Carvajal, Omar
Abstract: We studied the thermal physiology of the Andean lizard Stenocercus guentheri in order to evaluate the possible effects of global warming on this species. We determined the preferred body temperature ( T pref ), critical thermals (CTmin, CTmax), and hours of restriction and activity. T pref was 32.14±1.83 °C; CTmin was 8.31 °C in adults and 9.14 °C in juveniles, whereas CTmax was 43.28 °C in adults and 41.68 °C in juveniles. To assess extinction risk, we used the model created by Sinervo et al. (2010) and predicted that 16.7% of populations will have a high risk of extinction by 2020, with an increase to 26.7% by 2050. These results suggest that this species, despite being able to maintain its T pref through behavioral thermoregulation and habitat selection, could be physiologically sensitive to climate warming; thus, the potential for local adaptation may be limited under a warmer climate. Further studies focusing on the ability of S. guentheri to evolve higher T pref and thermal tolerances are needed to understand the ability of this species to respond to climate change. Highlights: We study the thermal physiology of an Andean lizard to assess effects of global warming. Stenocercus guentheri is physiologically sensitive to climate warming. 16.7% of populations have a high risk of extinction by 2020. 26.7% of populations have a high risk of extinction by 2050.